2017
DOI: 10.3897/natureconservation.20.12703
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the monitoring of Cerambyx cerdo

Abstract: Cerambyx cerdo is a longhorn beetle widely distributed in southern and central Europe. This saproxylic beetle is generally associated with oak forests where there are mature or partially dead and sun-exposed trees. Its populations are currently threatened by forest practices such as the removal of partially dead trees and the decline in the number of old oak trees situated in open or semi-open landscapes. Thus, C. cerdo has been included in Annexes II and IV of the Habitats Directive. The present paper is part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
22
0
3
Order By: Relevance
“…The species is widespread in most parts of Europe, but has become extinct in the United Kingdom and the Swedish mainland. During the last century the species suffered a dramatic decline in central Europe (Buse et al 2008, Zan et al 2017. In Poland C. cerdo has markedly declined, and today its occurrence is limited to areas west of the Vistula River, mainly in the western and southwestern parts of the country (Kadej et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The species is widespread in most parts of Europe, but has become extinct in the United Kingdom and the Swedish mainland. During the last century the species suffered a dramatic decline in central Europe (Buse et al 2008, Zan et al 2017. In Poland C. cerdo has markedly declined, and today its occurrence is limited to areas west of the Vistula River, mainly in the western and southwestern parts of the country (Kadej et al 2017).…”
mentioning
confidence: 99%
“…the edge of forests, meadows, dams of ponds) for reproduction (Buse et al 2008). During development, capricorn beetle larvae create holes and cavities (galleries) that are approximately 3.5 cm in diameter and up to 40 cm in length, and have a specific microclimate (Zan et al 2017). The corridor often ends with an approximately 10 cm wide oval cell.…”
mentioning
confidence: 99%
“…It is well known that some Coleoptera families and separate species have a clear preference for a certain forest layer (Su & Woods, 2001;Ulyshen, 2011;Procházka et al, 2018;Sheehan et al, 2019). A three-year study of the bait impact on Cerambyx cerdo Linnaeus, 1758 (Coleoptera) in Italy showed that this species was more common at a height of 10 m than at a height of 2 m (Redolfi De Zan et al, 2017). Traps in the forest understory caught the highest specimens' number of Xylotrechus colonus (Fabricius, 1775) and Graphisurus fasciatus (DeGeer, 1775), whereas more adults of Neoclytus mucronatus mucronatus (Fabricius, 1775) were caught in the forest canopy rather than in the understory layer (Wong & Hanks, 2016).…”
Section: The Trapping Rate Dependence On Traps Heightmentioning
confidence: 99%
“…Fermental traps with fermenting liquid baits (e.g. wine, molasses, beer with bananas, apples, sugar, and other natural fillers) have been shown to be effective in detecting many Coleoptera families (Williams et al, 1995;MacRae & Rice, 2007;Guarnieri, 2009;Shapovalov, 2012;Wong & Hanks, 2016;Redolfi De Zan et al, 2017;Egorov & Ivanov, 2018). Similar traps, where the process of active fermentation of sugars is taking place, also attract some other insect groups, in particular Lepidoptera (Devries & Walla, 2001;Dumbrell & Hill, 2005;El-Sayed et al, 2005; Barlow et al, 2007;Uehara-Prado & Freitas, 2009;Jakubikova & Kadlec, 2015), Hymenoptera (Dvořák, 2007;Sorvari, 2013Sorvari, , 2019Demichelis et al, 2014), Neuroptera (Duelli et al, 2006;Makarkin & Ruchin, 2019), Diptera (Dvořáková, 2008;Dvořák, 2014;Dvořák et al, 2017) and a number of other insects (Hongayo et al, 2014), as well as Gastropoda (Lucid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It typically lives in large, old trees (especially oaks) which are, at least partially, exposed to the sun. Redolfi De Zan et al (2017) provided details on biology, ecology and monitoring methods for this species.…”
Section: The Target Speciesmentioning
confidence: 99%